The Economic Potential of Aceh Cattle Based on Its Farmers, Traders, and Consumers Perspective - Sofyan, Hamny; Sudarnika, Etih; Satyaningtijas, Aryani S.; Sumantri, Cece; Agungpriyono, Srihadi (Frontiers in Sustainability, 2020)
This study aims to evaluate the economic potential of raising Aceh cattle from the perspective of farmers, traders and consumers through research conducted from June to August 2018 in Banda Aceh City and Aceh Besar District, Aceh Province. The survey was conducted through interviews and observations using a questionnaire that was given to 9 farmers, 23 traders and 22 consumers. Additional data collection was also carried out through related literature for deeper analysis. Data is presented descriptively and analyzed using strengths, weaknesses, opportunities and threats (SWOT) analysis. The results showed that there are some points in the strengths aspect of raising Aceh cows, i.e., high selling prices, easy maintenance and great tasting meat. The weaknesses consist of limited availability of feeder cattle, traditional methods used in assessing carcass weights when selling and buying Aceh cattle, as well as low cattle productivity compared to other cattle breeds. Opportunities that were identified were Aceh's demand for cattle meat, which is high on weekdays and religious holidays, the selling prices of cattle meat, which tended to increase and a government program to increase the productivity of local cattle. There are threats to raising Aceh cattle, i.e., the high price due to the difficulty in obtaining cattle meat, competition with other cattle breeds that have higher productivity, the existence of other sources of protein that are cheaper and consumers’ lower purchasing power. The difference between the strength and weakness factor shows a positive result (0.12), while the difference between the opportunity and threat factor shows a negative result (-0.29). These coordinate values indicate that the development production of Aceh cattle is still quite high, even though it has a threat that must be minimized. This study concludes that Aceh cattle has a high economic potential to be developed through improved breeding systems to increase the number of Aceh cattle breeds through price standardization policies, measurement of body weight using scales in the process of buying and selling cattle and increasing productivity. The government is expected to provide regulations to support farmers and traders so the Aceh cattle meat prices become more affordable for consumers.